Study the allelopathtic effect of the Harmala (Peganum harmala) on seed germination and seedling growth characteristics of new wheat cultivar of Gonbad compared to common wheat cultivar in Golestan Province. - علی راحمی کاریزکی; مسعود تاجی; نورمحمد رسایی; عظیم جمالی (علوم و فناوری بذر ایران)
Germination and seedling growth is one of the important processes that affect different plants allelopathic properties.Leaving crop residue on the soil surface can be caused production of phtochemicals that prevent from crop growth. In order to study the allelopathic effect of the Peganum harmalaon seed germination and seedling growth characteristicsof four wheat cultivar included of Morvarid, Kuhdasht, Gonbad and lin17 an experiment was conducted by a factorial Randomized complete design with four replicationsin the laboratory of Agricultural Faculty of Gonbad university. The treatments were included 4 concentrations harmal extract (0, 25, 50, and 75 percent) and four wheat cultivar's (Morvarid, Kuhdasht, Gonbad and lin17). The analysis of variance showed that the effect of cultivar, harmala extract concentration and interaction effects treatments were significant at 1% probability on all studied traits to exception seedling dry weight. Increasing harmala extract concentration had negative effect on all studied traits in all wheat cultivars.Means comparison in control levels showed that germination rate, beginning and end effective germination, germination percentage were not significantly difference among cultivars but Gonbad cultivar had less uniformity germination than other cultivars. Gonbadand Morvarid cultivars with 37% and 85% of germination had the highest and the lowest germination respectively.According to the results in control treatment, Morvarid andGonbad had the most seedling length, seedling vigor index and coefficient Allometry, butin 75% harmala extract concentration, Morvarid and Kouhdasht cultivars were better than others cultivars.